2016
DOI: 10.1136/jclinpath-2016-203945
|View full text |Cite
|
Sign up to set email alerts
|

Malignant peritoneal mesothelioma and Crohn disease

Abstract: Peritoneal MM occurs rarely in patients with IBD, but interestingly, has only been observed in the setting of CD and not in patients with ulcerative colitis. Chronic inflammation has been associated with the development of MM in rare instances and these three cases suggest that CD with transmural inflammation may also be a precursor. The precise role of CD-related transmural inflammation in the carcinogenesis of peritoneal MM remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Risk factors included asbestos exposure (4/16, 25%) and personal (5/15, 33%) and/or family (10/12, 83%) history of malignancy; however, genetic testing data were not available. Malignant peritoneal mesothelioma has been rarely described in other chronic inflammatory diseases involving the peritoneum including Crohn disease, familial Mediterranean fever-associated recurrent peritonitis, recurrent peritonitis secondary to diverticulitis and indwelling peritoneal catheters (13)(14)(15). Additional research is needed, but together these data suggest a possible role for chronic inflammatory peritoneal diseases such as endometriosis in promoting tumor progression in peritoneal mesothelioma.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors included asbestos exposure (4/16, 25%) and personal (5/15, 33%) and/or family (10/12, 83%) history of malignancy; however, genetic testing data were not available. Malignant peritoneal mesothelioma has been rarely described in other chronic inflammatory diseases involving the peritoneum including Crohn disease, familial Mediterranean fever-associated recurrent peritonitis, recurrent peritonitis secondary to diverticulitis and indwelling peritoneal catheters (13)(14)(15). Additional research is needed, but together these data suggest a possible role for chronic inflammatory peritoneal diseases such as endometriosis in promoting tumor progression in peritoneal mesothelioma.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in a model with Crohn's disease, it was also suggested that early inflammatory exudates might lead to the organization of layers of reactive mesothelial cells. [20]. This early reaction would be followed by subacute mesothelial cell proliferation [7].…”
Section: Discussionmentioning
confidence: 99%
“…Peritoneal mesotheliomas have been reported in the context of endometriosis, and the chronic inflammation [100] seen in these cases has been elicited as a possible etiopathogenetic factor, however, other factors, such as personal/familial history of malignancies could also predispose these patients in developing mesothelial malignancy [101]. Similarly, in a database of 3800 mesothelioma patients, three (0.08%) had Crohn disease, while no ulcerative colitis cases were found, also suggesting a role for the transmural inflammation in this context [102]. In the context of peritoneal inflammation, we should also be aware of the mesothelial cysts, formerly named "cystic mesothelioma", and the adenomatoid tumors, both mesothelial lesions potentially associated with inflammatory conditions [103,104], but usually of benign nature.…”
Section: Non-specific Pleuritismentioning
confidence: 96%